2012
DOI: 10.5402/2012/949427
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hypoadiponectinemia and Low Serum Concentrations of Calcium and Vitamin D in Women with Polycystic Ovary Syndrome

Abstract: Objective. To investigate the possible association of calcium and vitamin D deficiency with hypoadiponectinemia in women with PCOS. Subjects and Methods. In this case-control study, 103 PCOS cases and 103 controls included. The concentrations of calcium, 25-OH-vitamin D (25OHD), adiponectin, insulin, glucose, total cholesterol, HDL-cholesterol, triglyceride (TG), and androgens were measured in fasting blood samples. Results. Adiponectin (8.4 ± 2.7 ng/mL versus 13.6 ± 5 ng/mL in control group, P : 0.00), calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
44
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 32 publications
11
44
1
3
Order By: Relevance
“…While some studies reported lower levels of vitamin D in women with PCOS [46,47], other studies suggested that levels are comparable [48] or even higher compared to women with PCOS [49]. Several studies have reported an inverse relationship between body mass index (BMI) and vitamin D levels in PCOS patients [50][51][52].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…While some studies reported lower levels of vitamin D in women with PCOS [46,47], other studies suggested that levels are comparable [48] or even higher compared to women with PCOS [49]. Several studies have reported an inverse relationship between body mass index (BMI) and vitamin D levels in PCOS patients [50][51][52].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…The studies included premenopausal women (14-50 years) of various ethnicities, with the number of participants ranging from 45 to 400. Different stratifications were used: seven studies compared PCOS women with controls (19,20,22,23,24,27,28), three studies compared lean vs obese PCOS women (18,21,26), one study compared PCOS women with and without the metabolic syndrome (25), and one study solely included PCOS women (29). Large differences were found in the prevalence of vitamin D deficiency (defined as serum 25OHD levels !50 nmol/l), varying from 37% in a study carried out in Italy (21) to 72% in a study carried out in Scotland (19).…”
Section: The Association Between Vitamin D Status and Metabolic Distumentioning
confidence: 99%
“…In detail, three studies demonstrated a significantly lower serum 25OHD level in PCOS women: 32.4 vs 73.7 nmol/l in 90 PCOS women and 47 control women (24), 30.0 vs 43.7 nmol/l among 103 PCOS women and their controls (28), and 17.7 vs 79.2 nmol/l in 30 PCOS women and 15 control women (27). By contrast, another study among 291 PCOS women and 109 control women demonstrated a lower serum 25OHD level in control women than in PCOS women (53.5 vs 73.7 nmol/l) (23).…”
Section: The Association Between Vitamin D Status and Metabolic Distumentioning
confidence: 99%
See 2 more Smart Citations